DESIGN IN THE SYSTEM OF ART FORMS OF INFORMATION SOCIETY CULTURE - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Aesthetic nature of design as a spiritual culture phenomenon and an art form of information society is analyzed in the article.